2020
DOI: 10.1186/s12879-020-4844-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of virulence genes and phylogenetics of uropathogenic Escherichia coli among urinary tract infection patients in Addis Ababa, Ethiopia

Abstract: Background: Urinary tract infection (UTI) is a common cause of morbidity worldwide. Uropathogenic Escherichia coli (UPEC) bacteria are the major cause of urinary tract infections. UPEC strains derive from different phylogenetic groups and possess an arsenal of virulence factors that contribute to their ability to overcome different defense mechanisms and cause disease. The objective of this study was to identify phylogroup and virulence genes of UPEC among urinary tract infection patients. Methods: A cross sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
56
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 45 publications
32
56
1
3
Order By: Relevance
“…The most prevalent adhesin gene was fimH, followed by pap, sfa, and afa. In agreement with studies conducted in Ethiopia (Dadi et al, 2020) and Iran (Tajbakhsh et al, 2016), phylogenetic group B2 strains showed the highest frequency of the adhesin genes in our study. We found a coexistence of fimH and pap genes (69.2%), indicating a high presence of virulence genes among UPEC isolated from UTI patients in Thailand.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most prevalent adhesin gene was fimH, followed by pap, sfa, and afa. In agreement with studies conducted in Ethiopia (Dadi et al, 2020) and Iran (Tajbakhsh et al, 2016), phylogenetic group B2 strains showed the highest frequency of the adhesin genes in our study. We found a coexistence of fimH and pap genes (69.2%), indicating a high presence of virulence genes among UPEC isolated from UTI patients in Thailand.…”
Section: Discussionsupporting
confidence: 93%
“…The P-independent, X-binding fimbrial adhesin encoded by the afa1 operon mediates specific binding to uroepithelial cells and human erythrocyte receptors ( Labigne-Roussel & Falkow, 1988 ). Different studies have investigated the presence of the adhesion-encoding genes pap (P fimbriae), sfa (S fimbriae), afa (afimbrial adhesin), and fimH (type 1 fimbriae) across UPEC strains using multiplex PCR ( Rahdar et al, 2015 ; Dadi et al, 2020 ; Tarchouna et al, 2013 ; Shetty et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent adhesin gene was fimH, followed by pap, sfa, and afa. In agreement with studies conducted in Ethiopia (Dadi et al, 2020) and Iran (Tajbakhsh et al, 2016), phylogenetic group B2 strains showed the highest frequency of the adhesin genes in our study.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 93%
“…Our results are in accordance with several studies in which the dominant strain was found to be group B2. These studies were conducted in North America (45% prevalence of group B2) (Johnson et al, 2003), Denmark (67%) (Ejrnaes et al, 2011), Poland (35%) (Kot et al, 2016), South Korea (79%) (Lee et al, 2016), and Ethiopia (30%) (Dadi et al, 2020). Using a novel PCR-based method (Clermont et al, 2013), we could classify UPEC into groups C, E, and F and clade I, resulting in a lower percentage of strains in groups A, B1, and D than in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation